Stili navezanosti v odraslosti - Žvelc, Maša (Psihološka obzorja (Ljubljana), 2006)
Theory of attachment primarily described early relationships between a child and his caretakers. In the last twenty years there is a growing interest in adult attachment research. Theories and research findings of adult attachment stem from two different methodological approaches. The first approach measures adult attachment through Adult Attachment Interview (AAI; Main, 1991) where the attachment is assessed through the narratives of adult people of their early child experiences with their primary caretakers. The second approach measures adult attachment with the help of self-evaluative questionnaires, developed by (a) Hazan and Shaver (1987) who started this approach in the field of personality and social psychology, and (b) Bartholomew and Horowitz (1991). Research shows that there is significant correlation between early and adult attachment style. Attachment styles are passed from generation to generation. Basic adult attachment styles are: securely attached, preoccupied, fearful-avoidant, dismissing-avoidant and disorganized. Previous research using Barholomew and Horowitz (1991) Relationship Questionnaire on 176 Slovenian students showed that 48% students are securely attached, 29% are fearful-avoidant, 10% are dismissing-avoidant, and 13% have preoccupied attachment style. Theory of attachment is very useful for understanding the behavior and subjective experiences of children and adults. It is applicable to different contexts (psychotherapy, counseling, education .). The paper proposes further research focused on integration of adult attachment styles and types of object relations measured by Test of object relations (Žvelc, 1998) and Pictorial test of Separation andIndividuation (Žvelc, 2003).
Keywords: attachment; attachment theory; navezanost; odrasli; adult; interpersonal relations; medosebni odnosi; odraslost; stili navezanosti; psihologija; psychology